Atividade física e sintomas neuropsiquiátricos em pacientes com demência de Alzheimer Physical activity and neuropsychiatric symptoms in elderly with Alzheimer's dementia - Salma Stéphany Soleman Hernandez; Thays Martins Vital; Sebastião Gobbi; José Luiz Riani Costa; Florindo Stella (Universidade Estadual Paulista (UNESP), 2011)
Na demência de Alzheimer (DA) é comum a presença de sintomas neuropsiquiátricos resultantes de mudanças anatômicas e bioquímicas no cérebro. O objetivo deste estudo foi realizar uma revisão sistemática dos estudos que investigaram a relação entre atividade física e sintomas neuropsiquiátricos na DA. Efetuou-se uma pesquisa nas bases de dados: Academic Search Premier, Biological Abstracts, Medline, PsycINFO, Pubmed, Scielo, Science Direct, Sport Discus e Web of Science, utilizando-se as seguintes palavras - chave e operadores boleanos: (Neuropsychiatric disturbances OR Neuropsychiatric symptoms OR Neuropsychological disturbances OR Aberrant behavior OR Aberrant behaviour OR Behavior disturbances OR Behaviour disturbances OR Behavior management OR Behaviour management OR Disruptive behavior OR Disruptive behaviour) AND (Alzheimer) AND (Exercise OR Motor intervention OR training OR Physical activity OR fitness), além de referências cruzadas dos artigos selecionados. Foram encontrados oito estudos que preencheram os critérios de inclusão. Concluiu-se que bons resultados têm sido evidenciados para os distúrbios de agitação e sono de pacientes com DA. Entretanto então há um consenso de qual o melhor tipo de atividade para estes pacientes. Is common the presence of neuropsychiatric symptoms in Alzheimer's disease (AD), this is resulted of anatomical and biochemical changes in the brain. The objective of present study was to look for papers relating physical activity and neuropsychiatric symptoms through a systematic review. The following data bases was accessed: Academic Search Premier, Biological Abstracts, Medline, PsycINFO, Pubmed, Scielo, Science direct on line, Sport Discus and Web of Science, using the following key-words: (Neuropsychiatric disturbances OR Neuropsychiatric symptoms OR Neuropsychological disturbances OR Aberrant behavior OR Aberrant behaviour OR Behavior disturbances OR Behaviour disturbances OR Behavior management OR Behaviour management OR Disruptive behavior OR Disruptive behaviour) AND (Alzheimer) AND (Exercise OR Motor intervention OR training OR Physical activity OR fitness), besides crossing the references in the selected articles. Eight studies had filled the inclusion criteria. It was possible to conclude there are evidences of positive results for agitation and sleep disturbances in patients with AD. However, there's no consensus of what kind of activity is better for these patients.